Determining Young's modulus and Poisson's ratio of thin hard films. (August 2014) - Gong, M. F.; Qiao, S. R.; Mei, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Young's modulus and Poisson's ratio for thin hard films are quite difficult to measure by traditional testing methods. A series of equations for Young's modulus and Poisson's ratio of films are successfully deduced. A novel tensile process is described in this paper. It concludes that this process is relatively easy to perform and allows reliable determination of elastic constants for thin hard films. The magnitude of Young's modulus and Poisson's ratio for electroplating hard alumina film were 106–166 GPa and 0·26–0·27 respectively. Moreover, Young's modulus of film is influenced by the film's thickness and porosity level. The theoretical analysis is logical and reasonable.